Valuing the absence of feral swine in the United States: A partial equilibrium approach. (October 2018) - Holderieath, J.J.; Pendell, D.L.; Hadrich, J.C.; Anderson, A.; Slootmaker, C.; Harper, E.; Shwiff, S.A.
Abstract: Feral swine (also called wild pigs; Sus scrofa Linnaeus) are known to cause damage to crops among other types of property damage. This research addresses the lack of economic welfare estimates of wild pig imposed crop damages in the literature by estimating the value of wild pig removal with respect to five crops in nine southern U.S. states. An equilibrium displacement model was used to assess the changes in price and quantity that would result from eliminating damage to corn, soybeans, wheat, rice, and peanuts in these nine states. Changes in price and quantity were used to calculate the changes in producer and consumer welfare in both the short- and long-run. The total producer and consumer surplus gains were found to be $142 million in the short-run and $89 million in the long-run. Highlights: This study is the first to estimate welfare effects imposed by wild pig associated crop damage. The impact of wild pig imposed crop damage was found to be $142 million in the short-run and $89 million in the long-run. U.S. corn producers outside of the removal region bear most of the negative welfare effects at about $12.99/MT lost.